Envisioning New Jersey : An Illustrated History of the Garden State - Lurie, Maxine N., 1940-; Veit, Richard F., 1968- (Book collections on Project MUSE., 2016)
Envisioning New Jersey brings together over 650 spectacular images that illuminate the course of New Jersey history, from prehistoric times to the present. Maxine N. Lurie and Richard F. Veit, two leading authorities on New Jersey history, present here a smorgasbord of informative pictures that capture the amazing transformation of New Jersey over time.